Bioprocess Design Considerations for Cultured Meat Production With a Focus on the Expansion Bioreactor - Allan, Scott J.; De Bank, Paul A.; Ellis, Marianne J. (Frontiers in Sustainable Food Systems, 2019)
Cultured meat, as a cellular agriculture product, utilizes tissue engineering techniques and consequently faces not only cell culture challenges but also scale-up limitations. To ensure cultured meat is financially viable, efficient bioprocess design for scale-up is required. In this mini-review we focus on the design of the expansion bioreactor, and put it in context of the entire bioprocess by providing an overview of the upstream and downstream process considerations. As a full-scale cultured meat bioprocess is still hypothetical we include a review of the key factors and fundamental cell biology parameters required as input data for the design of a process with a product that is not only viable but price competitive. This review highlights the vital aspects of a cultured meat bioreactor design that are often overlooked when parallels are drawn against fermentation processes such as brewing or recombinant protein production in the pharmaceutical industry. Practical application and awareness of the concepts presented here will enable more accurate estimation of the production expenses and raw material requirements. This will form a basis for both further academic research and the design of industrial-scale processes in the field of cultured meat and the wider field of tissue engineering-based cellular agriculture.